Hi, I'm Sophie and I'm a Maths student at the University of Birmingham. I have always had a passion for maths due to the satisfaction you get from obtaining the one correct answer and the amount of real world applications it has. Hopefully you can gain a love for this subject too!
I am patient and able to offer real world explanations or simplified explanations of seemingly complicated maths as this is how I have gained my understanding of maths throughout my education. I have experience helping and teaching people of all ages as I ran orchestras and sports clubs in my spare time at secondary school and assisted a GCSE Maths class during my A Levels. This also helped me understand differences in the way people learn.
The focus of our sessions will be you! You will guide your own learning and what you would like us to cover in each session, and can come to me with any topic you need help with. I will ensure you have a sound understanding of all topics before moving onto harder questions and past exam papers. Exam practice is one of my strengths as I have completed every Core Maths past paper for the past 15 years and I will ensure you can access all the marks on a paper by clearly communicating your methods.
|Maths||A Level||£20 /hr|
|English Literature||GCSE||£18 /hr|
|-Personal Statements-||Mentoring||£20 /hr|
|Before 12pm||12pm - 5pm||After 5pm|
Please get in touch for more detailed availability
This is a typical gradient question for A2 papers, as it requires use of the Product Rule and Chain Rule, as well as knowledge of e^x.
Firstly, we can see that we will need to use the Product Rule as e^2-x and ln(3x-2) are being multiplied together. As the Product Rule is dy/dx= u.dv/dx + v.du/dx, we will also need to find out the differentials of e^2-x and ln(3x-2), where we let e^2-x = u and ln(3x-2) = v.
u=e^2-x This is 2 a combination of operations, meaning we will need the Chain Rule to obtain du/dx.If we let 2-x=t, then u=e^t. Differentiating 2-x mans that dt/dx= -1 and differentiating e^t means that du/dt remains e^t. The Chain Rule is du/dx=dt/dx*du/dt, meaning that du/dx=-1*e^t, and substituting t back into the eqution leaves us with du/dx=-e^2-x.
v=ln(3x-2) Again, we have 2 operations meaning the Chain Rule will be used to obtain dv/dx. If we let 3x-2=m, then v=ln(m). Differentiating 3x-2 means dm/dx=3, and differentiating ln(m) means dv/dm=1/m. Again, we will need to use the Chain Rule, dv/dx=dm/dx*dv/dm, meaning dv/dx=3*1/m. Substituting our m back into this equation leaves us with dv/dx=3/3x-2.
As we have now obtained our du/dx and our dv/dx, we cn use the Product Rule to find the gradient of our original function. The Product Rule is dy/dx=u.dv/dx+v.du/dx, meaning dy/dx=(e^2-x)(3/3x-2)+(ln(3x-2))(-e^2-x).
As we have an x value given to us in the question, we do not need to simplify this eqution and can cimply substitute our x value of 2 into this equation to find the gradient of the curve at that point. With our substituted x value of 2, dy/dx=(e^0)(3/4)+(ln(4))(-e^0)=(1)(3/4)+(ln(4))(-1). Therefore, our final answer is dy/dx=3/4-ln(4) at on the point on the curve where x=2. Using our Laws of Logarithms, this can also be written as dy/dx=3/4+ln(4)^-1=3/4+ln(1/4), and either answer would be ccepted in the exam.see more